Fenomena Aplikasi Pengolah Foto Digital pada Ponsel Pintar di Masyarakat Kota - Hendri Hartono; Dominikus Nunnun Bonafix (Humaniora, 2015)
Digital photography has recently developed rapidly. Apart from the development of film media to digital, digital itself develops significantly, especially in media aspect which a camera nowadays is not only used for taking pictures, but also can be implanted in other media, for instance smartphones or tablets. It is very common that mobiles have built-in cameras. The quality of image offered is getting better. The development of smartphone technology has reached to a certain capability to run an operational system as it is in computer media so that there are a lot of softwares or applications created. One of them is an application for photo editing. Photo editing applications in smartphones are created because of the development of applications in social media which is rapidly developed in mobile media. Social media has recently been a need for city people, in the fast and modern society. Social media is a media for interaction. One form of the interactions is photography which many applications in social media offering sharing photos fast and easily so that city people can update any or all activities or through photos which are uploaded in social media. Photo editing applications in smartphones eventually become the most downloaded applications. Therefore, people have more options to try or use various photo editing applications offering instant photo editing to suit their wish.